Isolation between electric and magnetic antennas in close proximity - Zhuang, Jingxin. (2009)
This final year report introduces the study of isolation between electric and magnetic antennas in close proximity. Monopole and slot antennas are used for electric and magnetic antennas respectively. Both antennas have been designed using High Frequency Structural Simulator (HFSS) and fabricated to verify the design concept. Measurement and simulation results are presented in this report for discussion.